Application prospect of speckle tracking echocardiography in pacemaker implantation - Nan Xu; Xiaoping Cheng; Lei Ren; Quan Yuan (Frontiers in Cardiovascular Medicine)
More than 1 million permanent pacemakers are implanted worldwide each year, half of which are in patients with high-grade atrioventricular block. Pacemakers provide adequate frequency support in the initial stage, but traditional right ventricular (RV) pacing may lead to or aggravate left ventricular dysfunction and arrhythmia. Several potential risk factors for heart failure and arrhythmias after pacemaker surgery have been identified, but their occurrence remains difficult to predict clinically. Compared with RV pacing, His bundle pacing (HBP) and left bundle branch pacing (LBBP) activate the intrinsic His–Purkinje conduction system and provide physiological activation, but whether HBP and LBBP also cause ventricular mechanical dyssynchrony remains uncertain. The implantation of cardiac resynchronization therapy and implantable cardioverter defibrillator depends on left ventricular ejection fraction (LVEF). LVEF This depends on volume changes and is less reproducible. Speckle tracking echocardiography (STE) is a technique that can accurately quantify the degree and duration of systolic deformation. STE detects changes in myocardial function more sensitively than traditional measures of diastolic and systolic function, including LVEF. Clinicians can evaluate myocardial strain and synchrony based on strain (percent change in segmental length from baseline) and strain rate (strain per unit time). This review and case series investigate the clinical use of speckle tracking echocardiography in pacemaker implantation.